Deep-Time Images in the Age of Globalization
VII, 317 p. 97 illus., 85 illus. in color.
Keywords: This open access volume explores the impact of globalization on the contemporary study of deep-time art. The volume explores how early rock art research’s Eurocentric biases have shifted with broadened global horizons to facilitate new conversations and discourses in new post-colonial realities. The book uses seven main themes to explore theoretical, methodological, ethical, and practical developments that are orienting the study of Pleistocene and Holocene arts in the age of globalization. Compiling studies as diverse as genetics, visualization, with the proliferation of increasingly sophisticated archaeological techniques, means that vast quantities of materials and techniques are now incorporated into the analysis of the world’s visual cultures. Deep-Time Images in the Age of Globalization aims to promote critical reflection on the multitude of positive – and negative – impacts that globalization has wrought in rock art research. The volume brings new theoretical frameworks as well as engagement with indigenous knowledge and perspectives from art history. It highlights technical, methodological and interpretive developments, and showcases rock art characteristics from previously unknown (in the global north) geographic areas. This book provides comparative approaches on rock art globally and scrutinises the impacts of globalization on research, preservation, and management of deep-time art. This book will appeal to archaeologists, social scientists and art historians working in the field as well as lovers of rock art. .